Pothole detection using lightweight network models - Abdullah, S. M.; Hasan, Shakib Al; Parsa, Antara Firoz; Kabbya, MD. Asif Shahidullah; Talukder, Anika Hasan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.